Peranan Hukum Dalam Optimalisasi Pendapatan Negara Dari Sektor Pertambangan Mineral Dan Batubara Untuk Kesejahteraan Rakyat - Agustinus, Ivan Ferdiansyah (Journal of Comprehensive Science, 2025)
The Preamble to the Constitution of the Republic of Indonesia emphasizes that Indonesia adheres to the welfare state system, where the state is responsible for the welfare of its people. In an effort to prosper the Indonesian people with hundreds of millions is not an easy thing, the budget deficit from year to year shows the need to increase state revenue, but the increase in revenue cannot rely on the tax sector, therefore it is necessary to increase state revenue from other sectors including the mineral and coal mining sector. The next question is what is the role of law in optimizing state revenue from the mineral and coal mining sector? The research method used is normative-empirical research, the theory used is the theory of the welfare state and the theory of the legal system (Lawrence M. Friedman), based on the results of the research, it is concluded that if the legal system has affected mineral and coal mining income, this can be observed by the existence of several changes in the legal system in the form of changes in laws and regulations, related institutions and legal culture and its impact on the improvement of the law State revenues so far. In addition to having a positive impact on state revenue, it also has a negative impact including environmental damage, social conflicts and the rise of illegal mining.